Agentes inteligentes artificiais - Nakamiti, Eduardo Kiochi (2009)
The diffusion of Artificial Intelligent Agents, superficially considered as elements that have independent thinking and whose decisions influence processes in the everyday human reality increasingly known, especially in electronic media, the users of banking services, on access to telephone service in our home appliances and entertainment. Its presence is sometimes felt by the ease of access to resources often so powerful and sometimes so unnoticed. It can be perceived in a negative way, when access to electronic banking services is denied without explanation. Much of learning today, relies on Internet and getting information online without the help of search engines is disappointing. Today, these mechanisms offer more than simply the result of a search. They seem to have the intelligence to offer suggestions in relation to our interest. This form of communication that are incorporating to their customs, is strongly influenced by known agents, in computer systems. In this work, we will make a history of its appearance, and technological innovations and cultural, primarily focusing on the first Artificial Intelligence in order to built a clear, detailed view of the Artificial Intelligent Agents, at present, and to establish a hypothetical path for future developments. The methodological basis of work is based on the complexity of the issue addressed. Such complexity refers to tools and distinct views, dynamic and interactive, pointing to the computer and its various aspects, the artificial intelligence and its tools, the cyber arena of interdisciplinarity as the first and, to the environment and the semiotic analysis tool of the production and mediation of knowledge and theories of complexity. The corpus of the analysis and interpretation are circumscribed to the phenomenon of Artificial Intelligent Agents of nowadays and of the future, but for both, and according to the methodology adopted, the fields of knowledge are inspected more in the expectation of higher fidelity description. The main conclusion is the remarkable trend of spraying and increasing invisibility of Artificial Intelligent Agents, as elements of support in decision making and control of the environment and the information we received